(untitled) (Research, Society and Development, 2020)
This article addresses the complexity of secularism in the education Mozambican society, paying special attention to the analysis of the Concordat signed between the States of Mozambique and Vatican, 2012. This agreement contains the authorization for the “Catholic Religious Education” (CRE) linked to Catholic Church is held in any Mozambican school unit. The theme requires deepening and sociological investigation because it´s a tension between the notion of secularism that the recent secular state of democratic law, also based on “respect and guarantee of fundamental rights and freedoms”, expresses in its Magna letter and, the Concordat that provides the National Education System for proselytizing actions inserted in a confessional system offered to the population. The problem makes it possible to reflect on the international Catholic strategy with Portuguese-speaking countries, as well as to relate the adoption of CRE in schools / units that provide education services contracted by the Mozambican government to the general population. In view of the local religious plurality and the imposition of the CRE in the respective schools. The research was carried out in a bibliographic, electronic and documentary way (May, 2004) from a qualitative perspective with the theoretical basis of Social Sciences and Sociology of Religions. Therefore, the confessional offer, established by the International Concordat between the Vatican and Mozambique, and the resulting dynamics, in addition to contributing to the weakening of religious plurality and, therefore, of democracy, make education a field of religious disputes in the country as well.